Implementação e análise de um sistema fotovoltaico com módulos de silício multicristalino instalados em solo em propriedade rural - Osorio, Edson Alexandre Arévalo (2019)
The use of distributed generation photovoltaic systems has grown considerably in Brazil, and every day more systems are connected to the grid. This work presents the development and analysis of a photovoltaic system of 20 kWp ground-mounted in a rural property associated with the Consolata Agroindustrial Cooperative located in the west of Paraná, using photovoltaic modules of multicrystalline silicon. System simulation was performed using the PV * SOL Premium program, establishing the best location for installation, with the optimum angle of inclination of the PV array at 18 º, estimated productivity of 1612 kWh/kWp and performance ratio of 85.2 %. The photovoltaic modules were electrically characterized under standard conditions and they all had nominal power above the catalog value. Facility inspections and measurements in loco were performed using calibrated solar cells and thermographic camera to compare data obtained through simulations and the data acquisition system. Inspections and tests were performed in the grounding system, through the potential drop method, using a digital earth tester. Productivity and performance ratio (PR) were determined for 12 months of operation of the photovoltaic system where it was observed that the measured PR was only 4.2 % smaller than the simulated one. Finally, the study of the economic feasibility, presented a 9 years pay-back of investment for ground-mounted PV system.